2003
DOI: 10.1046/j.1469-8137.2003.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Heteromorphic incompatibility retained in self‐compatible plants produced by a cross between common and wild buckwheat

Abstract: Summary• Common buckwheat ( Fagopyrum esculentum ) is a dimorphic self-incompatible plant with either a pin or a thrum flower. It is considered that self-incompatibility, flower morphology, and pollen size are governed by the S supergene.• Here, we produced self-compatible buckwheat lines by an interspecific cross between F. esculentum and F. homotropicum with embryo rescue.• The flower morphology of these lines was long homostyle and pollen size was similar to that of thrum. Pollen size of F 1 plants produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…They postulated that the S supergene of buckwheat consists of five genes: G, style length; I S , stylar incompatibility; I P , pollen incompatibility; P, pollen size; and A, anther height (Fig. 2) We found that a self-compatible line that was produced by an interspecific cross between common buckwheat and F. homotropicum shows the pollen-style interaction in accordance with the S supergene hypothesis 9 . The flower morphology is long homostyle (Fig.…”
Section: S Supergene Hypothesis and Breakdown Of Selfincompatibility supporting
confidence: 73%
“…They postulated that the S supergene of buckwheat consists of five genes: G, style length; I S , stylar incompatibility; I P , pollen incompatibility; P, pollen size; and A, anther height (Fig. 2) We found that a self-compatible line that was produced by an interspecific cross between common buckwheat and F. homotropicum shows the pollen-style interaction in accordance with the S supergene hypothesis 9 . The flower morphology is long homostyle (Fig.…”
Section: S Supergene Hypothesis and Breakdown Of Selfincompatibility supporting
confidence: 73%
“…A recent experiment, conducted by Matsui et al (2003), also supported the hypothesis and suggested that F. homotropicum, an unusual self pollinating species, has arisen by a past recombination event in the S gene complex. In order to clarify the molecular mechanism of the heteromorphic self-incompatibility system and its evolution, a large insert size library with enough genomic coverage is necessary to clone the entire S locus, for both S and s haplotypes.…”
Section: Pcr Screening and Library Coveragementioning
confidence: 82%
“…This inheritance pattern was first proposed for the genus Primula, where there is evidence that three to five, or more, linked genes occur (Ernst, 1955;Dowrick, 1956;Lewis and Jones, 1992;Kurian and Richards, 1997;Barrett and Shore, 2008). There is more limited evidence supporting the occurrence of a supergene in lineages outside the Primulaceae that have independently evolved distyly, including Fagopyrum (Woo et al, 1999;Matsui et al, 2003;Fesenko et al, 2006;Wang et al, 2005) and Turnera, where the inheritance of self-compatible homostyles has been investigated (Shore and Barrett, 1985;Barrett and Shore, 1987;Tamari et al, 2001Tamari et al, , 2005.…”
Section: Introductionmentioning
confidence: 94%